2016
DOI: 10.1038/srep38850
|View full text |Cite
|
Sign up to set email alerts
|

Profiling bacterial communities associated with sediment-based aquaculture bioremediation systems under contrasting redox regimes

Abstract: Deposit-feeding invertebrates are proposed bioremediators in microbial-driven sediment-based aquaculture effluent treatment systems. We elucidate the role of the sediment reduction-oxidation (redox) regime in structuring benthic bacterial communities, having direct implications for bioremediation potential and deposit-feeder nutrition. The sea cucumber Holothuria scabra was cultured on sediments under contrasting redox regimes; fully oxygenated (oxic) and redox stratified (oxic-anoxic). Taxonomically, metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 46 publications
0
27
0
Order By: Relevance
“…Furthermore, bacterial production during detrital breakdown may have contributed variably to the nutrition of juveniles between treatments through the constant release of bioavailable compounds. Studies have demonstrated that systems with oxic‐anoxic sediment conditions produced Holothuria scabra sea cucumbers with significantly higher biomass compared to animals grown in oxic treatments (Robinson et al, ; Robinson, Caldwell, Jones, Slater, & Stead, ). These studies concluded that the anaerobic condition in redox‐stratified sediments was more suitable for holothurian culture because it produced considerable amounts of extracellular, low molecular weight organic compounds that may be important for sea cucumber nutrition.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, bacterial production during detrital breakdown may have contributed variably to the nutrition of juveniles between treatments through the constant release of bioavailable compounds. Studies have demonstrated that systems with oxic‐anoxic sediment conditions produced Holothuria scabra sea cucumbers with significantly higher biomass compared to animals grown in oxic treatments (Robinson et al, ; Robinson, Caldwell, Jones, Slater, & Stead, ). These studies concluded that the anaerobic condition in redox‐stratified sediments was more suitable for holothurian culture because it produced considerable amounts of extracellular, low molecular weight organic compounds that may be important for sea cucumber nutrition.…”
Section: Discussionmentioning
confidence: 99%
“…Sediment microbial communities are primarily net heterotrophic systems that link energy transfer to higher trophic levels; therefore recycling nutrients in situ may provide a viable means to intensively culture deposit feeders with a higher overall efficiency (Schroeder, 1987). Furthermore, prior research (Robinson et al, 2015;Robinson et al, 2016) demonstrated that redox-stratified sediment supported faster growth rates and a higher biomass yield of Holothuria scabra relative to fully oxic sediment, indicating that heterotrophic systems are more favourable for deposit feeder growth.…”
Section: Introductionmentioning
confidence: 88%
“…Slater and Carton 2007;Watanabe et al, 2012;Neofitou et al, 2019;Zamora et al, 2016). In particular, their ability to selectively extract specific components of sedimentary organic matter, such as bacteria, nitrogen and transparent exopolymer particles (Moriarty 1982;Roberts et al, 2003;Robinson et al, 2016;Sadeghi-Nassaj et al, 2018), may suggest that their use in co-culture systems is relevant. Indeed, their use can contribute to remediate or manage the risks associated with pond sediment degradation in aquaculture ponds, where high densities and/or dystrophy conditions typically result in animal health issues (Lemonnier et al, 2006;Lemonnier, 2007).…”
Section: Introductionmentioning
confidence: 99%